Analysis of Umer Chapra thought on Islamic monetary instruments in Indonesia: a vector autoregressive (VAR) and vector error correction model (VECM) approach - Ahlis, Fatoni; Adam Sa'ad, Auwal; Ridzuan, Nurharena; Rosman, Romzie (Albukhary International University, 2023)
Economic growth and exchange rate stability are each state's goals in the Islamic monetary system. Therefore, there is a need to develop effective instruments to support the achievement of the monetary objectives. This study aimed to determine the effect of Islamic monetary instruments variables proposed by Umer Chapra on economic growth and exchange rate stability in Indonesia, the amount of influence of each variable, and how significant the influence exerted by each variable. M. Umer Chapra is a Modern Muslim economist trying to popularise the Islamic economic system, including the Islamic monetary policy. The originality of the paper lies in its combination of various statistical tests and analyses to examine the relationships among the variables studied. Through utilising VAR/VECM approach, the results showed that deposit money has a negative impact on economic growth while M0 and SRR provide a positive impact. However, for the stability of the exchange rate, all variables (LNM0, LNDM and SRR) shows a negative trend towards exchange rate stability.